Spontaneous variation regarding grape berry skin color: A comprehensive study of berry development by means of biochemical and molecular markers. (July 2017) - Ferreira, Vanessa; Fernandes, Fátima; Carrasco, David; Hernandez, Marivel Gonzalez; Pinto-Carnide, Olinda; Arroyo-García, Rosa; Andrade, Paula; Valentão, Patrícia; Falco, Virgílio; Castro, Isaura
Abstract: Understanding grape berry development and the metabolism of different classes of compounds responsible for traits like berry's color is imperative to control and improve quality aspects of grapes. A colorimetric, biochemical and molecular characterization allowed the comprehensive description of the pigment-related characteristics of nine berry skin color somatic variants, belonging to four different varieties. Although the observed berry skin color variability was not fully explained by MybA locus, the phenolic profiles allowed inferring about specific interferences among the biosynthetic pathways. Data were consistent concerning that grapes showing cyanidin-3- O -glucoside as the major anthocyanin and flavonols with two substituent groups in the lateral B-ring are generally originated by a white ancestor. After retro-mutation, these grapes seem to keep the dysfunction on flavonoid hydroxylases enzymes, which negatively affect the synthesis of both flavonols and anthocyanins with three substituent groups in the lateral B-ring. Overall, the obtained results indicate that the color differences observed between somatic variants are not solely the result of the total amount of compounds synthesized, but rather reflect a different dynamics of the phenolic pathway among the different color variants of the same variety. Chemical compounds: Gallic acid (PubChem CID: 370); Caftaric acid (PubChem CID: 6, 440, 397); Catechin (PubChem CID: 73, 160); Epigallocatechin gallate (PubChem CID: 65, 064); Quercetin-3- O -galactoside (PubChem CID: 5, 281, 643); Quercetin-3- O -glucoside (PubChem CID: 25, 203, 368); Malvidin-3- O -glucoside (PubChem CID: 443, 652); Peonidin-3- O - p -coumaroylglucoside (PubChem CID: 44, 256, 849); Malvidin-3- O - p -coumaroylglucoside (PubChem CID: 44, 256, 988); Resveratrol-3- O -glucoside (PubChem CID: 25, 579, 167). Graphical abstract: Highlights: Somatic variants with differences in skin color appearance were studied during berry development. Integrative analyses, combining colorimetric, HPLC and molecular profiles. Relationship between skin color and phenolic content was suggested. Phenolic profiles revealed specific interferences/dysfunctions on the phenols biosynthesis. Heterozigosity of the VvMybA1–2 non-functional allele was found in colored variants.